The Role of commercial banks towards building local content capacity in upstream oil and gas industry in Kenya - Omune, Herbert Okundi (Strathmore University, 2019)
The discovery of commercially viable crude oil reserves in Kenya in 2012 and the delineation of “Oil, Gas and Other Minerals” as a new sector in the economic pillar of Kenya Vision 2030 suggests that the country is poised to start engaging in notable activities in upstream oil and gas. It is expected that oil exploration companies and the Government will identify and target local content initiatives as a means to create and share value from the exploitation of oil and gas deposits in Kenya. A robust and resilient banking sector in Kenya will be essential for the growth of local content capabilities in upstream oil and gas. This research study therefore sought to establish the extent to which the services currently provided by commercial banks in Kenya support local content development in upstream oil and gas sector in the country. The study recognizes that the upstream oil and gas sector is highly capital intensive and financing activities in this sector also involve unique, complex risks, which may require specialised knowledge. For this reason, the research study also sought to determine the lending capabilities of commercial banks in Kenya in financing upstream oil and gas transactions. The final objective of the study was to determine the strategies that commercial banks in Kenya can adopt to effectively support local content capabilities in upstream oil and gas. The research study employed both qualitative and quantitative approach. The primary target population of the study were commercial banks in Kenya. The source of primary data and unit of analysis were individual professionals within the banking industry. Data was collected through semi structured questionnaires. Additional data was also collected through interviews with the Kenyan oil and gas contractors in upstream oil and gas sector to validate the findings from the banking industry. The findings from the research study indicated that commercial banks have a major role to play in the development of local content capabilities in the upstream oil and gas industry. However, most banks lacked the technical capability to assess counterparty risks, formulate risk mitigation structures and provide solutions that can meet the unique requirements of the upstream oil and gas sector. The research study recommends that commercial banks adopt an ecosystem approach to offering banking services to local enterprises venturing into upstream oil and gas. The study proposes that further research be done to establish the initiatives that the Government of Kenya can introduce to encourage the use of commercial banks in Kenya in financing transactions in upstream oil and gas.
A Thesis submitted in partial fulfillment of the requirements for the award of the Degree of Masters of Business Administration at Strathmore University Business School
Keywords: Commercial banks; Local content capacity; Oil and gas industry_Kenya